Peniruan Trend Korea Pada Gen Z - Rizkiyah, Adinda Zulfa; Fahmi, Muhammad Ikhsan; Rajabi, Jibran Aufa; Nisa, Pia Khoirotun (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research aims to determine the increasing imitation of Korean cultural trends which are increasingly hot. Korean culture, which is currently trending in Indonesia, has spread to teenagers or Gen Z, starting from hairstyles, Korean fashion, and everything that smells Korean. The author examines the imitation of Korean trends among Gen Z, where Gen Z has extensive knowledge of Korean trends so that their application of imitation is also very strong. The method used in this research is qualitative with literature study. The object of this research discusses the strong imitation of Korean trends among Gen Z and Gen Z's knowledge about Korea which originates from the mass media.